Inspiratory Muscle Training Based on Anaerobic Threshold on the Functional Capacity of Patients After Coronary Artery Bypass Grafting: Clinical Trial - Cordeiro,André Luiz Lisboa (2020)
Abstract Introduction: Coronary artery bypass grafting (CABG) is associated with reduced ventilatory muscle strength and consequent worsening of functional capacity (FC). Inspiratory Muscle Training (IMT) can be indicated, but there is still a lack of knowledge about the use of the anaerobic threshold (AT) as a basis for prescription. The objective of this study is to evaluate if IMT based on AT modifies FC and inspiratory muscle strength of patients submitted to CABG. Methods: This is a clinical trial. On the first postoperative day, the patients were divided into two groups: the conventional group (IMT-C), which performed IMT based on 40% of maximal inspiratory pressure (MIP), and the IMT-AT group, which performed IMT based on AT. All patients underwent preoperative and postoperative assessment of MIP and performed a six-minute walk test (6MWT). Results: Forty-two patients were evaluated, 21 in each group. Their mean age was 61.4±10 years and 27 (64%) of them were male. There was a reduction of inspiratory muscle strength with a delta of 23±13 cmH2O in the IMT-C group vs. 11±10 cmH2O in the IMT-AT group (P<0.01) and of the walking distance with a delta of 94±34 meters in the IMT-C group vs. 57±30 meters in the IMT-AT group (P=0.04). Conclusion: IMT based on AT minimized the loss of FC and inspiratory muscle strength of patients submitted to CABG.